Sports Information Communication Model Based on Network Technology - Shao, Guohua (Mobile networks and applications, 2022)
Aiming at the sports information service platform of communication subject, communication object and media are analyzed, on this basis from the perspective of statistics in sports as an example to analyze the characteristics of information and channel sink. By using the analytic hierarchy process, from the network sports information content, audience experience, network sports information organization and dissemination of sports information and network environment in four aspects construct the sports information dissemination model evaluation index system, and determine the weight of each index. The results show that: the premise of sports information dissemination model based on network technology in order to serve the public, the right to guide the public to build a harmonious sports information network for the purpose of the business model, to the development of sports website, expand business partners, re positioning the sports network station commercial operation mode, break the old ideas, improve the connotation of operation mode sports website.